Effects of time since invasion and control actions on a coastal ecosystem invaded by non‐native pine trees. Issue 1 (6th March 2022) - Mesacasa, Letícia; Macagnan, Leonardo Bruno; Fiaschi, Pedro; Dechoum, Michele de Sá
Abstract: Invasive non‐native trees cause structural and functional changes in plant communities, which tend to increase over time since invasion. Native vegetation responses after control operations provide important information for restoration. We evaluated the effects of time since invasion and of pine control on plant community structure and on functional traits in a coastal open ecosystem in southern Brazil. We compared richness, diversity, abundance and cover of woody and non‐woody native plant species, as well as species composition and community‐weighted means (CWM) based on functional traits (dispersal syndrome, fruit type, maximum height and shade tolerance) of plant communities, in four conditions: a non‐invaded area, an area where pines were controlled (managed area), an area of recent invasion and an area invaded longer ago. Woody species abundance, richness and diversity declined over time since invasion. However, while abundance recovered to the point of not differing from the non‐invaded condition in areas where pines were controlled, species diversity and richness were lower in the managed area than in the area that was never invaded. The effects of pine invasion on richness and diversity of non‐woody plants did not increase over time, but plant cover progressively diminished. Woody and non‐woody species composition varied between the four conditions. Species composition similarity was lower between conditions for non‐woody than for woody species. CWM differed between the older invasion and the other conditions, determined especially by native plant height and shade tolerance. Taller plants and more shade tolerant native species were exclusively sampled in the older invasion. Synthesis and application: Pine invasion reduced species abundance, plant cover, richness and diversity, altering the composition of plant community. The escalation of negative temporal effects of pine invasion was observed on the composition of woody and non‐woody species and on functional traits. Although pine control favoured the natural regeneration of non‐woody species, diversity of woody species in the area submitted to pine control was lower than in the non‐invaded condition. Restoration activities are therefore required to increase woody species diversity. These results provide relevant guidance for the restoration of coastal ecosystems following invasive pine control. Abstract : Pine invasion reduced native species abundance, plant cover, richness and diversity, with an increase over time since invasion. Species diversity and richness were lower in the managed area than in the area that had not been invaded. Restoration activities are therefore required to increase native species diversity. Resumo: Árvores exóticas invasoras causam profundas mudanças estruturais e funcionais em comunidades vegetais, as quais tendem a se acentuar em função do tempo de invasão. Respostas da vegetação nativa ao controle de espécies exóticas invasoras fornecem embasamento importante para a restauração de áreas invadidas. Nós avaliamos o efeito do tempo de invasão e do controle de Pinus elliottii em parâmetros estruturais e funcionais de comunidades vegetais em um ecossistema costeiro no sul do Brasil. Comparamos riqueza, diversidade, abundância e cobertura de espécies nativas lenhosas e não lenhosas, assim como a composição de espécies e CWM ( community‐weighted means ) com base em atributos funcionais (síndrome de dispersão, tipo de fruto, altura máxima, tolerância à sombras) dessas comunidades vegetais, em quatro condições: área não invadida, área previamente invadida e na qual o controle de pínus foi realizado, área invadida recentemente e área invadida há mais tempo. A abundância, riqueza e diversidade de espécies de espécies lenhosas declinaram com o aumento do tempo de invasão. Entretanto, enquanto a abundância foi recuperada em áreas onde os pínus foram controlados, não diferindo de áreas não invadidas, a riqueza e a diversidade de espécies lenhosas foram menores em áreas nas quais o controle foi feito quando comparadas às áreas não invadidas. Os efeitos em termos de riqueza e diversidade de espécies não lenhosas não foram acentuados com o tempo de invasão, mas a cobertura diminuiu progressivamente. A composição de espécies lenhosas e não lenhosas variou entre as quatro condições. Uma menor similaridade da composição de espécies entre as condições foi observada para espécies não lenhosas do que para espécies lenhosas. CWM diferiu entre a invasão mais avançada e as demais condições, determinada especialmente pela altura e pela tolerância à sombra. Plantas mais altas e espécies tolerantes à sombra foram exclusivamente amostradas na área de invasão mais avançada. Síntese e aplicações. A invasão por pínus levou à redução em abundância, cobertura, riqueza e diversidade de espécies, alterando a composição de espécies em comunidades invadidas. A intensificação dos efeitos temporais negativos da invasão foi observada na composição de espécies lenhosas e não lenhosas e na estrutura funcional das comunidades vegetais. Apesar das ações de controle terem favorecido a regeneração natural de espécies não lenhosas, a diversidade de espécies lenhosas foi menor em áreas submetidas ao controle quando comparadas com áreas não invadidas. Assim, ações de restauração são necessárias para aumentar a diversidade de espécies lenhosas. Esses resultados provêem diretrizes para a restauração de ecossistemas costeiros após o controle de árvores exóticas invasoras.